Integrating a voting protocol within an argumentation-based BDI System - Sosa Toranzo, Cecilia (2010)
BDI models are powerful tools that can play a fundamental role in implementing intelligent systems for complex business and industrial problems. Besides, it has also been recognized the benefits achieved when integrating BDI models with different reasoning formalisms, like for instance argumentation or case-based reasoning. Several multi-agent systems have been proposed where voting-based protocols have proven to be efficient mechanisms to lead to a coordinated social result. Likewise, there are several works where these protocols have also been applied as internal processes that arise in one agent’s mind. Following these trends, the main contribution of this work it to integrate voting jointly with argumentation into a BDI system to implement the agent’s deliberative aptitudes. All the concepts involved in this proposal are exemplified by working with a travel assistant agent developed with freely available technologies.